Urgensi Hermeneutika Sebagai Metode Dalam Pemahaman Hadis - Suryani, Suryani (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Urgency of Hermeneutics as a Method in Understanding Hadith Hadith as a Source of Law must be understood comprehensively, in order to be applied to every age, using the right approach method, among the methods of approaching understanding hadith is the hermeneutics of hadith. Hermeneutics, which was originally developed as a method of interpretation of the text of scripture in the West, developed into the most important method of approach in the field of interpretation of religious texts including hadith texts. Therefore, this study aims to describe and analyze the concept and urgency of hermeneutics in the understanding of hadith which serves as a method for contextualizing the understanding of hadith. The scope of this article is hermeneutics as a method of understanding hadith, to find the moral idea or moral message contained in a hadith. This research is qualitatively descriptive by analyzing sources starting with a narrative about the concept of hermeneutics as a method of understanding and the urgency of hermeneutics as a method in understanding hadith with a descriptive method of analysis. The results showed that hermeneutics as a method of understanding hadith emphasizes the objectivity of the initiator or source of the hadith, analyzing things related to the anchor or text known as the tradition of criticism of sanad hadith, looking for moral ideas from the hadith text by connecting the micro text or hadith with the context of society macro. Meanwhile, the urgency of hermeneutics as a method of understanding hadith is to actualize the messages contained in the understanding of hadith so that they can be actualized in the current context.